Prior Preterm Birth and Birthweight Below the 5th Percentile are Independent Risk Factors for Recurrence of a Small for Gestational Age Neonate - Mor Svorai; Barak Aricha; Offer Erez; Chun-Ying Guo; Yang Pan (Wolters Kluwer Health, 2020)
Abstract. Objective:. This study aimed to determine: (1) whether recurrent deliveries of a small for gestational age (SGA) neonate are associated with increased obstetrical or neonatal complications; (2) whether the risk factors that can predict small for gestational age (SGA) recurrence. Methods:. This study was based on Soroka Medical Center's Obstetrics electronic database. The database consisted of 109 022 women who had 320 932 deliveries between the year 1988-2014.The study cohort included 6.8% (7 368/109 022) of these patients who gave birth to a singleton SGA neonate on their first delivery and had more than one delivery. The study population was divided into two groups according to the outcome of the subsequent delivery: (1) women with sporadic SGA who delivered a non-SGA neonate (n = 5 416); (2) women with recurrent SGA (n = 1 952). SGA defined as birthweight <10th percentile. Maternal and neonatal complications were compared between the two groups. Logistic regression was used to determine independent risk factors for SGA recurrence. Results:. The prevalence of birthweight <5th percentile was higher among the recurrent SGA group in the first delivery (P < 0.001). Bedouin ethnicity was more prevalent in the recurrent SGA group (P < 0.001). The rate of preterm delivery was higher in the first delivery of the recurrent SGA group (P = 0.015). The sporadic SGA group had a higher rate of perinatal mortality during the first pregnancy (P = 0.017). The rate of severe hypertension (P = 0.005), polyhydramnios, meconium-stained amniotic fluid, nonreassuring fetal heart rate and total perinatal mortality (P < 0.001) were higher in the second delivery of the recurrent SGA group. In a logistic regression model, preterm delivery and birthweight <5th percentile at the first delivery was found to be independent risk factors for recurrence of an SGA neonate in the subsequent birth (relative risks:1.530, confidence interval: 1.249-1.875; relative risks:1.826, confidence interval: 1.641-2.030, respectively). Conclusion:. Women with recurrent SGA neonates have specific clinical characteristics. Among women who deliver an SGA neonate, preterm delivery, and birthweight <5th percentile are independent predictors for its recurrence.